M. I. Akilina – Scientist and Person - M. Ya. Dvorkina (Библиосфера)
The Biography of the well-known Russian librarian and scientist Maria Ivanovna Akilina is presented. It is prepared on the basis of her autobiography and other documents of the Human Resources Department of the Russian State Library. The main scientific works of M. I. Akilina are characterized. The subjects of scientific works of the scientist are revealed: scientific and methodological activity of libraries, theoretical problems of library science, national libraries of the republics of the Russian Federation and central libraries of the constituent entities of the Russian Federation, mass, rural libraries. The periodicals in which M. I. Akilina published, her awards are named. The personal qualities of Maria Ivanovna are shown.